EXPLORING THE RELATIONSHIP BETWEEN SCREEN DEPENDENCY DISORDER AND PSYCHOLOGICAL WELL-BEING AMONG ADOLESCENTS: A LITERATURE REVIEW - Nur Haffiza Rahaman; Liley Afzani Saidi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Screen Dependency Disorder (SSD) arises from the uncontrolled excessive utilization of electronic devices and the internet, resulting in psychological well-being disorders. Despite the recognized impact of social media on adolescents’ psychological well-being, insufficient comprehensive research has been conducted on this issue. Hence, this paper seeks to analyze the current literature regarding the adverse effects of social media usage on adolescent psychological well-being, particularly emphasizing the perspective of screen dependency disorder (SSD). The study’s results found that parental knowledge and control affect adolescent screen time. This article suggests that a key aspect of promoting healthy screen time habits for adolescents is setting clear boundaries and limits. Parents can establish rules around when and how long their adolescents are allowed to use screens, as well as what types of content are appropriate.